Dorsal Root Entry Zone Lesioning for Brachial Plexus Avulsion Injuries: Case Series and Literature Review - Chalil, Alan; Wang, Qian; Abbass, Mohamad; Santyr, Brendan G.; MacDougall, Keith W.; Staudt, Michael D. (Frontiers in Pain Research, 2021)
Introduction: Brachial plexus avulsion (BPA) injuries commonly occur secondary to motor vehicle collisions, usually in the young adult population. These injuries are associated with significant morbidity, and up to 90% of patients suffer from deafferentation pain. Neuromodulation procedures can be efficacious in the treatment of refractory neuropathic pain, although the treatment of pain due to BPA can be challenging. Dorsal root entry zone (DREZ) lesioning is a classical and effective neurosurgical technique which has become underutilized in treating refractory root avulsion pain. Methods: A systematic review of the different technical nuances, procedural efficacy, and complication profiles regarding DREZ lesioning for BPA injuries in the literature is included. We also present an institutional case series of 7 patients with BPA injuries who underwent DREZ lesioning. Results: In the literature, 692 patients were identified to have undergone DREZ lesioning for pain related to BPA. In 567 patients, the surgery was successful in reducing pain intensity by over 50% in comparison to baseline (81.9%). Complications included transient motor deficits (11%) and transient sensory deficits (11%). Other complications including permanent disability, cardiovascular complications, infections, or death were rare (less than 1.9%). In our case series, all but one patient achieved greater than 50% reduction in pain intensity, with the mean pre-operative pain of 7.9±0.63 (visual analog scale) reduced to 2.1±0.99 at last follow-up (p<0.01). Conclusion: Both the literature and the current case series demonstrate excellent pain severity reduction following DREZ ablation for deafferentation pain secondary to BPA.